Fixed Point Theorems for Cyclic Weakly Contraction Mappings in Dislocated Quasi Extended b-Metric Space. (6th August 2019) - Nurwahyu, Budi
Abstract : In this paper, we establish and prove some theorems about existence and uniqueness of fixed point for cyclic weakly contraction mappings in dislocated quasi extended b -metric space.